Widow spiders in the New World: a review on Latrodectus Walckenaer, 1805 (Theridiidae) and latrodectism in the Americas - Caruso,Marjolly Brigido (2021)
Abstract Humankind has always been fascinated by venomous animals, as their toxic substances have transformed them into symbols of power and mystery. Over the centuries, researchers have been trying to understand animal venoms, unveiling intricate mixtures of molecules and their biological effects. Among venomous animals, Latrodectus Walckenaer, 1805 (widow spiders) have become feared in many cultures worldwide due to their extremely neurotoxic venom. The Latrodectus genus encompasses 32 species broadly spread around the globe, 14 of which occur in the Americas. Despite the high number of species found in the New World, the knowledge on these spiders is still scarce. This review covers the general knowledge on Latrodectus spp. from the Americas. We address widow spiders’ taxonomy; geographical distribution and epidemiology; symptoms and treatments of envenomation (latrodectism); venom collection, experimental studies, proteome and transcriptome; and biotechnological studies on these Latrodectus spp. Moreover, we discuss the main challenges and limitations faced by researchers when trying to comprehend this neglected group of medically important spiders. We expect this review to help overcome the lack of information regarding widow spiders in the New World.